Modern Adaptation Strategies to Water Scarcity Amidst Climate Change in the Southeastern Oases of Morocco. - Abdessamad khouya (Journal of Pure & Applied Sciences, 2025)
The study focused on the oases of southeastern Morocco, which are characterized by an arid and desert climate throughout the year, according to established scientific metrics. The results showed that rainfall trends are moving toward drought and water scarcity, leading to a decline in water resources and a decrease in river flow and groundwater levels. Historically, the inhabitants of the oases managed to adapt to water scarcity through traditional techniques, social organizations, and customary laws. However, these methods have seen a decline in recent decades, replaced by modern technologies such as contemporary pumping stations. These shifts, along with climate change, have contributed to significant environmental changes, including the reduction of groundwater levels and reserves, the drying up of traditional irrigation systems (khattaras), the neglect of vast areas of palm groves, and the acceleration of phenomena like desertification and hydrological drought. In conclusion, the study emphasizes that water is the lifeblood of the oases, and that the efficient management and conservation of these resources must be a top priority to ensure the sustainability of the oases.